Mycobacterial infections in European wild boar (Sus scrofa) in the Czech Republic during the years 2002 to 2005 - I. Trcka; J. Lamka; R. Suchy; M. Kopecna; V. Beran; M. Moravkova; A. Horvathova; M. Bartos; I. Parmova; I. Pavlik (Veterinární Medicína, 2006)
A total of 842 wild boar of differing ages, originating from 29 (37.7%) of the 77 districts in the Czech Republic, were examined during the hunting seasons from 2002 to 2005. Of them, 274 (32.5%) of the animals were wild specimens and 568 (67.5%) from game parks. Out of 786 animals, the following were included in the study: 668 piglets, 61 juveniles, 32 adult males and 25 adult females. A total of 2 704 samples from various tissues and faeces were examined: 309 separately collected faecal samples from 309 (36.7%) animals, 2 332 samples from various tissues and 63 faecal samples from 533 (63.3%) animals. Mycobacteria were isolated from 75 (8.9%) animals from 11 of the districts. Neither a causative agent of bovine tuberculosis, nor any other members of Mycobacterium tuberculosis complex were isolated from any of the animals. From one (0.1%) animal, M. avium subsp. paratuberculosis of IS900 RFLP type A-C10 was isolated from intestinal lymph nodes, which was also isolated within the same district during other studies of cattle and free living ruminants. The causative agent of avian tuberculosis, M. a. avium (IS901+ and IS1245+), was isolated from 7 (0.8%) animals; among them tuberculous lesions were detected in intestinal lymph nodes, with gross tuberculous lesions visible on two animals. The causative agent of avian mycobacteriosis M. a. hominissuis (IS901- and IS1245+) was detected in lymph nodes without gross lesions in one (0.1%) animal. From 45 (5.5%) animals without lesions, atypical mycobacteria of the following nine species were isolated from pulmonary lymph nodes, small and large intestine, intestinal mucosa and faeces: M. fortuitum, M. chelonae, M. scrofulaceum, M. triviale, M. terrae, M. phlei, M. abscessus, M. flavescens, and M. smegmatis. Due to a high density of wild boar and their large migration radius, they can be viewed as a potential source for mycobacterial infections as well as other infectious agents.